INTER-RELIGIOUS RELATIONSHIP BETWEEN HINDUS AND MUSLIMS IN LOMBOK - Miftahur Ridho (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
Despite its heterogeneous population, Lombok is well known for its reputation as Pulau Seribu Mesjid (island of thousand mosques).The idea of thousand mosques reflects the strong notion of Islam as the main identity marker. This, however, often brings uneasiness for both conflict between Muslim and non-Muslim, and between Muslims groups living in the island.This paper, aims at mapping out the triangular relationships between Hindus, Wetutelu Muslims, and Waktu Lima Muslims in Lombok, an island where a significant number of Balinese Hindus live as religious minority among SasakMuslims majority. In this paper, I argue that inter-religious relationship between Hindus and WetuteluMuslims is harmonious, while that between Hindus and Waktu Lima orthodox Muslims is marked by hostility. However, the inter-religious relationship between Hindus and the less orthodox Waktu Lima Muslims represent a number of uncertainties.